Ubiquitin Specific Protease 15 Has an Important Role in Regulating Grain Width and Size in Rice. Issue 1 (22nd February 2019) - Shi, Cuilan; Ren, Yulong; Liu, Linglong; Wang, Fan; Zhang, Huan; Tian, Peng; Pan, Tian; Wang, Yongfei; Jing, Ruonan; Liu, Tianzhen; Wu, Fuqing; Lin, Qibing; et al.
Abstract : OsUBP15, encoding a ubiquitin-specific protease15, regulates grain width and size in rice. Abstract: Ubiquitination and deubiquitination are reversible processes that play crucial roles in regulating organ size in plants. However, information linking deubiquitination and seed size in rice ( Oryza sativa ) is limited. Here, we characterized a dominant large-grain mutant, large grain1-D ( lg1-D ), with a 30.8% increase in seed width and a 34.5% increase in 1, 000-grain weight relative to the wild type. The lg1-D mutant had more cells oriented in the lateral direction of the spikelet hull compared with the wild type. Map-based cloning showed that LG1 encodes a constitutively expressed ubiquitin-specific protease15 (OsUBP15) that possesses deubiquitination activity in vitro. Loss-of-function and down-regulated expression of OsUBP15 produced narrower and smaller grains than the control. A set of in vivo experiments indicated that the mutant Osubp15 had enhanced protein stability relative to wild-type OsUBP15. Further experiments verified that OsDA1 directly interacted with OsUBP15. Genetic data indicated that OsUBP15 and GRAIN WIDTH 2 ( GW2 ) were not independent in regulating grain width and size. In summary, we identified OsUBP15 as a positive regulator of grain width and size in rice and provide a promising strategy for improvement of grain yield by pyramiding OsUBP15 and gw2 .